Transient transmission of Chikungunya virus in Singapore exemplifies successful mitigation of severe epidemics in a vulnerable population. (September 2021) - Hapuarachchi, Hapuarachchige Chanditha; Wong, Wing-Yan; Koo, Carmen; Tien, Wei-Ping; Yeo, Gladys; Rajarethinam, Jayanthi; Tan, Eugene; Chiang, Suzanna; Chong, Chee-Seng; Tan, Cheong-Huat; Tan, Li-Kiang; Ng, Lee-Ching
Highlights: Chikungunya virus genetic data suggested unsustainable local transmission. Aedes albopictus was the primary vector of outbreak strains. Population exposure to Chikungunya virus remained low despite two local outbreaks. Epidemics can be averted with robust surveillance and vector control strategies. Abstract: Objectives: Singapore experienced two major outbreaks of chikungunya in 2008-09 and 2013-14. Despite repeated virus introductions, fresh local outbreaks have not emerged after 2014. The present study reviews the success of chikungunya control in Singapore, despite repeated introduction of virus strains, presence of competent vectors and an immunologically naïve population. Methods: Chikungunya virus (CHIKV) sequences (421 envelope 1 genes and 56 polyproteins) were analysed to distinguish the indigenous virus groups from 2008 to 2020. Vector surveillance data was used to incriminate the vector/s associated with local outbreaks. The population exposure to CHIKV was determined by assessing the seroprevalence status in three cohorts of sera collected in 2009 (n=2, 008), 2013 (n=2, 000) and 2017 (n=3, 615). Results: Four distinct groups of CHIKV of East, Central and South African genotype have mainly circulated since 2008, transmitted primarily by Aedes albopictus . The age weighted CHIKV IgG prevalence rates were low (1-5%) and showed a non-significant increase from 2009 to 2013, but a significant decrease in 2017. In contrast, the prevalence of CHIKV neutralising antibodies in the population increased significantly from 2009 to 2013, with no significant change in 2017, but the levels remained below 2%. Conclusions: The evidence suggested that surveillance and vector control strategies implemented were robust to avert severe epidemics, despite repeated introduction of virus strains, presence of competent vectors and an immunologically naïve population.